The impact of early massive galaxy formation on the cosmic microwave background - Eda Gjergo; Pavel Kroupa (Nuclear Physics B)
The Cosmic Microwave Background (CMB) anisotropies, corrected for foreground effects, form the foundation of cosmology and support the Big Bang model. A previously overlooked foreground component is the formation of massive early-type galaxies (ETGs), which can no longer be ignored, particularly in light of JWST's detection of massive, evolved systems at extreme redshifts (z>13). The rapid formation of massive ETGs has been advocated in galaxy evolution studies for decades, and recent evidence has compelled even proponents of hierarchical mass assembly to acknowledge the fact that massive ETGs evolve quickly. Constraints from chemical evolution are particularly stringent. Without both intense star formation and a top-heavy galaxy-wide initial mass function of stars (IMF), it is difficult to reconcile stellar population synthesis models with the high metallicity and abundance patterns of α-elements. We infer from previous studies that the progenitor cloud of each massive ETG must have had a radius of ≈400 kpc. Comparing this value to the average present-day separation of massive ETGs, their formation may have occurred around 15<z<20. We consider this epoch of formation in a flat-ΛCDM cosmological context, incorporating the known and necessary properties of massive ETGs – properties encapsulated independently by the integrated galaxy-wide IMF (IGIMF) theory. The massive ETG evolution presented in this work is consistent with recent advancements in stellar and galaxy evolution, and is derived entirely without priors or constraints from the CMB. Yet, it emerges as a non-negligible source of CMB foreground contamination. Even in our most conservative estimates, massive ETGs account for 1.4% up to the full present-day CMB energy density.